2014
DOI: 10.1103/physrevb.89.045423
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of bound states in graphene point contacts

Abstract: Electronic localization in narrow graphene constrictions are theoretically studied, and it is found that long-lived (∼ 1 ns) quasi-bound states (QBSs) can exist in a class of ultra-short graphene quantum point contacts (QPCs). These QBSs are shown to originate from the dispersionless edge states that are characteristic of the electronic structure of generically terminated graphene in which pseudo time-reversal symmetry is broken. The QBSs can be regarded as interface states confined between two graphene sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The origin of these resonances is attributed to the formation of quasi-bound states near the aperture due to the interference of edge states. 53 A typical behavior of lowestenergy resonance for N c ≪ N z is displayed in Fig. 4(c) Its width at the maximum is scaled with N z following a power law, Γ −1 ∼ N 3 z , in agreement with our analytical treatment.…”
Section: B Resonant Transport Through An Aperturesupporting
confidence: 81%
See 1 more Smart Citation
“…The origin of these resonances is attributed to the formation of quasi-bound states near the aperture due to the interference of edge states. 53 A typical behavior of lowestenergy resonance for N c ≪ N z is displayed in Fig. 4(c) Its width at the maximum is scaled with N z following a power law, Γ −1 ∼ N 3 z , in agreement with our analytical treatment.…”
Section: B Resonant Transport Through An Aperturesupporting
confidence: 81%
“…4 (a)]. This type of aperture was studied by us 53 and it was analytically shown that peculiar low-energy resonant states could form due to the presence of edge states. In what follows, we revisit this phenomenon by a mode-matching approach.…”
Section: B Resonant Transport Through An Aperturementioning
confidence: 99%
“…18 Quantum point contacts for the GNR have been studied extensively by various groups. [19][20][21][22][23][24][25] Deng et al 25 predicted that long lived quasi-bound states originate from the dispersion-less edge states due to the electronic structure of generically terminated graphene. These quasibound states accounted for the interface states between two graphene sheets, and it was shown that their properties can be changed with the size and geometry of the interface contact.…”
Section: Introductionmentioning
confidence: 99%
“…The main feature of these states is that they are spread in a narrow energy window, so any electron from the leads injected at these energies easily passes across the system. 45,72 FIG. 10 The DFT calculations are performed within the superlattice approach using the density functional based tightbinding method implemented by the DFTB+ code 73 with the associated Slater-Koster parameters.…”
Section: Final Remarksmentioning
confidence: 99%